Nacionalne in politične razmere v Kanalski dolini pred in med prvo svetovno vojno. Primer Ukev - Cvirn, Janez (Zgodovinski časopis, 2000)
At the beginning of the 20th century the German National Party in southern Carinthia in Austria politically dominated even the municipal areas with the predominantly Slovene population. A typical example of the prevailing political and national circumstances in Val Canale (Kanalska dolina) and elsewhere in Austrian southern Carinthia was the area of Ugovizza (Ukve), a municipality in which, according to population censuses, the majority of its predominantly Slovene population had always used Slovene as the colloquial language. The most radical exponents of the national struggle in Ugovizza were local priest Jožef Kukočka who, althought Czech by birth, was strongly in favor of Slovenes, and on the other hand a thin layer of village magnates such as the local innkeeper (who was also the major of Ugovizza), or the local teacher. The differences between them became extremely pronounced during the First World War when secular and military authorities started a planned percesution of nationally conscious Slovenes, espacially the clergy.
Keywords: Kukačka, Jožef, 1865-1937; Kanalska dolina; zgodovina; history; narodne manjšine; narodnostno vprašanje; politična geografija; slovenska manjšina; Ukve; 1911/1918